2018
DOI: 10.1080/20004508.2018.1541675
|View full text |Cite
|
Sign up to set email alerts
|

New immigrants. An incentive for intercultural education?

Abstract: This study was inspired by an inclusive intercultural perspective on education, and developed empirical knowledge concerning the intercultural professional development of in-service teachers. The study was conducted during the first year of a newly-designed master's programme that focused on "education for refugees". In the Netherlands master's programmes in education qualify inservice teachers to contribute to school development, together with giving them a specialisation in a specific topic. The findings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
3
18
0
4
Order By: Relevance
“…Familiarity with these pedagogies rather depended on teachers´previous life and professional experiences as well as self-initiation, rather than a shared vision on cultural and linguistic diversity in pedagogy that PD could facilitate. This finding adds to previous indications that teachers need pedagogical support in the classroom in meaningfully developing classroom strategies related to cultural diversity and support student learning (Leeman andvan Koeven 2018, Forghani-Arani et al 2019).…”
Section: Scattered Commitment and Collaborationsupporting
confidence: 77%
See 2 more Smart Citations
“…Familiarity with these pedagogies rather depended on teachers´previous life and professional experiences as well as self-initiation, rather than a shared vision on cultural and linguistic diversity in pedagogy that PD could facilitate. This finding adds to previous indications that teachers need pedagogical support in the classroom in meaningfully developing classroom strategies related to cultural diversity and support student learning (Leeman andvan Koeven 2018, Forghani-Arani et al 2019).…”
Section: Scattered Commitment and Collaborationsupporting
confidence: 77%
“…PD focusing on emotional aspects often develops cultural sensitivity and positive intergroup relations by engaging in interactive, cooperative activities. As mentioned before, rather than segmenting the aims and contents of PD for cultural diversity, it is suggested to see PD as a system aiming at transformation, integrating critical reflection and supporting teachers in finding pedagogical responses (Szelei and Alves 2018, Creemers et al 2013, Leeman and van Koeven 2018. Forghani-Arani et al (2019) add the need for PD to persistently reconnect practice to theory, to be driven by teachers and supported by school leaders.…”
Section: Professional Development For Cultural Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Translating this approach to interculturality, this research has recognized the importance of promoting, during the educational trajectory at the university, a wide variety of learning experiences with which to learn about cultural diversity, teachers being aware of their roles as education professionals, and understanding the complexities they will encounter when working in multicultural contexts. These data are consistent with other studies [8,24,[33][34][35][36][37], which emphasize the need to open university classrooms to the intercultural reality, as a way to promote experiential learning and provide students with the necessary tools to work optimally on interculturality during their professional careers.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in education indicate that there has been very little preparation in the teacher training process for learning the intercultural dimension, developing intercultural communication skills, and enriching cultural knowledge (Byram, 2014;Gorski, 2012;Lázár, 2011). However, other researchers (Bringle, Hatcher, & Jones, 2011;Leeman & Koeven, 2018;Schutte, 2018) found that educators who met directly with people from (Agmon-Snir & Shemer, 2016;Deardorff, 2006Deardorff, , 2011Fantini, 2007;Malewski et al, 2012;Stephan & Stephan, 2013) other cultures and were exposed to an ethnically-culturally diverse environment opened their eyes and developed cultural sensitivity and emotion. Bradford, Allen, and Beisser (2000) have indicated that the concept of "intercultural competence" is defined as knowledge, skills, attitudes and policies developed by professionals in ongoing learning processes in order to create effective work with people from different cultures in various fields, such as communication, psychology, linguistics, anthropology and education.…”
Section: Intercultural Competencementioning
confidence: 99%